Parameters Affecting Household Income Diversity of Farmer’s Tribes in South Sumatra Tidal Wetland - Elisa Wildayana; M.S. Imanudin; H. Junedi; Mohd. Zuhdi; M Edi Armanto (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: The research aimed to determine parameters affecting household income diversity of farmer’s tribes in South Sumatra tidal wetland, especially studied from the aspect of land acreage, education level, age of farmers and tribes of farmers. The research was using survey method and carried out from June-August 2016 in the Delta Telang I Banyuasin, South Sumatra. The data were recorded by questionnaire for 145 respondents of farmers. Data was processed, described and correlated to see the relevance of the parameters with other parameters. The research concluded that the character of household economy of farmers explaining the relation between production decisions to increase rice production is land acreage, education, age, experience of farmers, number of household members, and labor allocation. Multi commodities farming (rice and plantation) was very favorable compared to monoculture rice fields? But this is a little bit contradictive with government policy that the research area is pointed out as the center of rice production. Therefore, government policy needs to motivate farmers that they can manage their farming from upstream to downstream and they work full in their own farming. The government policy should be site-specific and appropriated with the tribes of farmersKeywords: Household, income, diversity, tribes, tidal wetlandAbstrak (Indonesian): Penelitian ini bertujuan untuk menentukan parameter yang mempengaruhi keragaman pendapatan rumah tangga suku petani di lahan pasang surut Sumatera Selatan, terutama dari aspek luas lahan, tingkat pendidikan, usia dan suku petani. Metode penelitian adalah survey lapangan yang dilakukan pada bulan Juni-Agustus 2016 di Delta Telang I Banyuasin. Data direkam dengan kuesioner untuk 145 responden. Data diproses, dijelaskan dan dibuat korelasi untuk melihat hubungan parameter satu dengan parameter lainnya. Hasil penelitian menyimpulkan bahwa ekonomi rumah tangga petani menentukan keputusan untuk berproduksi. Produksi padi ditentukan oleh luas lahan, pendidikan, usia, pengalaman petani, jumlah anggota rumah tangga, dan alokasi tenaga kerja. Pertanian multicropping (padi dan perkebunan) sangat menguntungkan dibandingkan dengan monokultur padi, akan tetapi hal ini sedikit bertentangan dengan kebijakan pemerintah bahwa daerah penelitian telah ditetapkan sebagai sentra produksi padi. Oleh karena itu, perlu kebijakan pemerintah untuk memotivasi petani untuk tetap monokultur padi, tetapi petani harus mengelola pertaniannya mulai dari hulu sampai ke hilir. Kebijakan pemerintah ini harus bersifat spesifik dan disesuaikan dengan suku-suku petani.Kata kunci: Rumah tangga, pendapatan, keanekaragaman, suku, pasang surut